THE 7TH NFC AWARD IN PAKISTAN AND ITS IMPLICATIONS FOR KHYBER PAKHTUNKHWA: AN ANALYSIS - Altaf Hussain; Dr. Waqar Ahmed; Asif Ali Shah (International Journal of Contemporary Issues in Social Sciences, 2024)
The 7th National Finance Commission (NFC) Award, announced in 2010, marked a significant shift in Pakistan’s fiscal federalism by redistributing financial resources among the federal government and provinces, including Khyber Pakhtunkhwa (KP). This study critically examines the implications of the 7th NFC Award for KP, focusing on its economic, social, and political impacts. The Award’s revised formula increased the provincial share from the divisible pool to 57.5%, introduced multiple criteria for revenue distribution beyond population, and recognized KP’s contributions and vulnerabilities, particularly due to its strategic role in counterterrorism. The analysis highlights that while the increased financial allocations have bolstered provincial autonomy, enhanced development spending, and improved public service delivery in KP, challenges remain in terms of fiscal management, revenue generation, and addressing intra-provincial disparities. The study also explores how the Award has influenced KP’s ability to fund critical sectors such as education, health, and infrastructure, ultimately contributing to regional stability and socio-economic progress. However, despite these gains, the province continues to face significant challenges, including dependency on federal transfers, inadequate capacity to generate own-source revenues, and complexities in managing the impact of militancy and displacement on its fiscal needs. The paper concludes with recommendations for enhancing the effectiveness of the NFC Award in KP, advocating for increased fiscal responsibility, capacity building, and the need for a more dynamic formula that adapts to evolving provincial needs. By analyzing the multifaceted implications of the 7th NFC Award, this study provides a comprehensive understanding of its impact on KP and offers insights into the ongoing discourse on equitable fiscal federalism in Pakistan.